Reward and threat in the adolescent brain: implications for leadership development. Issue 4 (5th June 2017) - Riddell, Patricia M.
Abstract : Purpose: In the last 10 to 15 years, research studies have focused on the effects of differences across generations that result in differences in cultural expectations within the workplace (e.g.Arsenault, 2004 ). Different generations create shared attitudes to work and preferences for types of work which result in differences in their perception of, for instance, what makes a good leader or even the value of leadership within an organisation. While these generational differences are real, these analyses do not take into account differences that might result from the age, and therefore developmental stage, of the populations being assessed. The neuroscience literature clearly shows that there are maturational differences in the brain which are not complete until late teens to early 20s. It is therefore possible that some of the generational differences result from differences in processing ability resulting from structural immaturities in the brain. In particular, there are differences in the rate of maturation of areas of the brain related to reward sensitivity, threat sensitivity and regulation of behaviour which result in substantial differences in behaviour from adolescence through into adulthood. The purpose of this paper is to consider the effect of maturational changes in the brain on behaviours related to leadership and to outline ways in which these changes can be addressed in order to encourage young people to develop as leaders. This will include providing suitable experiences of leadership to encourage the faster development of the neural structures which underlie these capabilities. Design/methodology/approach: Recent advances in neural imaging have resulted in a substantial increase in research investigating the development of the brain during adolescence. A literature review was conducted to find adolescent research that investigated decision making and risk taking. The data obtained were integrated and implications for leadership were drawn from an analysis of the resulting theoretical framework. Findings: The research into decision-making processes in adolescents and younger adults points to a number of ways in which these differ from mature decision making. Younger people: (find it harder to inhibit behaviours) are more responsive to immediate reward; are more optimistic about the outcome of risky decisions; and are more responsive to social rewards (Jones et al., 2014). They also lack the experiences that adults use to distil the gist of a situation and therefore are more dependent on conscious, cost-benefit analysis of the outcome of decisions. Practical implications: An understanding of the differences between adult and adolescent decision making points to the role of experience as a key factor in mature decision making. If adolescents are to make mature decisions, they have to be offered suitable challenges in safe environments from which they can gain expertise in leadership decision making. These can be designed to account for differences in sensitivity to reward and punishment in this group. In addition, young adults would benefit from learning the gist interpretations that have been extracted from situations by experienced leaders. This suggests that adolescents and adults would benefit from simulated leadership experiences and leadership mentoring. Social implications: The Baby Boomer generation who currently hold many of the leadership positions in organisations are coming close to requirement. They will have to be replaced by members of Generation X and the Millennial Generation resulting in potentially younger leaders. In addition, flatter organisational structures that are currently being implemented in many organisations will require leadership at many more levels. Thus, we need to be able to develop leadership skills in a more diverse and younger section of society. Understanding how the brain develops can help us to design appropriate leadership experiences and training for this upcoming generation of young leaders. Originality/value: Recent advances in neuroscience of adolescence provide a unique opportunity to bring new evidence to bear on our understanding of decision making in young adults. This provides practical implications for how to develop leadership within this group and to support them as they gain experience in this domain. The evidence also points to a benefit for the increased risk taking seen in adolescence since this leads to greater motivation to try new, and potentially risky, ventures. Through a better understanding of the differences in decision making, we can both help adolescents to develop more mature decision making faster while benefitting from the optimism of youth.